Influence of row spacing and organic nutrient management practices on growth, yield and nutrient uptake of chia (Salvia hispanica) - K M, PRAVALIKA; S B, YOGANANDA; P, THIMMEGOWDA; P S, FATHIMA; M A, ANANTH KUMAR (The Indian Journal of Agricultural Sciences, 2024)
The field experiment was conducted during rainy (kharif) seasons of 2020–21 and 2021–22 at Zonal Agricultural Research Station, Vishweshwaraiah Canal Farm, Mandya, Karnataka, to study the consequences of row spacing and organic nutrient management practices on growth, yield and nutrient uptake of chia (Salvia hispanica L.). The experiment was conducted in a factorial randomized complete block design (Factorial-RCBD), with 12 treatment combinations replicated thrice. The treatments comprised of 2 spacings (45 cm × 15 cm and 60 cm × 15 cm) and 6 organic nutrient management practices [application of 75 and 100% recommended dose of nitrogen (RDN) equivalent compost along with the application of Jeevamrutha at sowing and 30 days after sowing (DAS)]. The pooled mean results of 2-years revealed that row spacing and organic nutrient management practices significantly influenced the performance of chia. Plant height, number of branches/plant, total dry matter production, and yield variables such as spike number and spike length were all significantly greater in 60 cm × 15 cm spacing with the application of 100% RDN equivalent compost + application of Jeevamrutha at sowing and 30 DAS. The same treatment also recorded significantly higher nutrient uptake (66.35, 12.91, and 52.27, NPK kg/ha, respectively). Whereas, significantly higher seed yield (1015.47 kg/ha) and leaf area index (1.72) were gained with 45 cm × 15 cm + 100% RDN equivalent compost + application of Jeevamrutha at sowing and 30 DAS.